Akt2/LDLr double knockout mice display impaired glucose tolerance and develop more complex atherosclerotic plaques than LDLr knockout mice. (12th November 2013) - Rensing, Katrijn L.; de Jager, Saskia C.A.; Stroes, Erik S.; Vos, Mariska; Twickler, Marcel Th.B.; Dallinga-Thie, Geesje M.; de Vries, Carlie J.M.; Kuiper, Johan; Bot, Ilze; von der Thüsen, Jan H.
Abstract: Aim: To characterize the phenotype of Akt2/low-density-lipoprotein receptor double knockout (dKO) (Akt2/LDLr dKO) mice with respect to insulin resistance and features of atherosclerotic plaque progression. Methods and results: Metabolic profile and atherosclerotic plaque progression were compared between LDLr KO mice and Akt2/LDLr dKO mice. Total cholesterol, glucose, and insulin levels were significantly higher and oral glucose tolerance test (GTT) was more impaired in Akt2/LDLr dKO mice than in LDLr KO mice. Although atherosclerotic plaques at both the carotid artery and the aortic root of Akt2/LDLr dKO mice were significantly smaller ( P < 0.05) compared with LDLr KO controls, plaque composition in these mice was more complex, showing 34–50% reduced collagen content ( P < 0.01), 1.4-fold larger necrotic cores ( P < 0.05) and six-fold more TUNEL-positive cells ( P < 0.01). In situ zymography revealed a more than two-fold higher gelatinolytic activity in Akt2/LDLr dKO mice ( P < 0.05). In vitro analyses showed that deletion of Akt2 caused decreased migration, proliferation, and collagen content of vascular smooth muscle cells (VSMCs) and disturbed the balance of metalloproteinases (MMPs) and tissue inhibitor of metalloproteinase (TIMP) mRNA expression in macrophages and VSMCs. Conclusion: Akt2/LDLr dKO mice develop insulin resistance and complex atherosclerotic lesions. These phenotypic characteristics make Akt2/LDLr dKO mice an interesting mouse model to study the effects of insulin resistance on the development and progression of atherosclerosis.